A case of early-onset diabetes with impaired insulin secretion carrying a PAX6 gene Gln135* mutation. (18th August 2022) - Sekiya, Motohiro; Yuhara, Mikiko; Murayama, Yuki; Ohyama Osawa, Mariko; Nakajima, Rikako; Ohuchi, Nami; Matsumoto, Nako; Yamazaki, Daichi; Mori, Sayuri; Matsuda, Takaaki; Sugano, Yoko; Osaki, Yoshinori; et al.
Abstract : Summary: A paired homeodomain transcription factor, PAX6 (paired-box 6), is essential for the development and differentiation of pancreatic endocrine cells as well as ocular cells. Despite the impairment of insulin secretion observed in PAX6-deficient mice, evidence implicating causal association between PAX6 gene mutations and monogenic forms of human diabetes is limited. We herein describe a 33-year-old Japanese woman with congenital aniridia who was referred to our hospital because of her uncontrolled diabetes with elevated hemoglobin A1c (13.1%) and blood glucose (32.5 mmol/L) levels. Our biochemical analysis revealed that her insulin secretory capacity was modestly impaired as represented by decreased 24-h urinary C-peptide levels (38.0 μg/day), primarily explaining her diabetes. Intriguingly, there was a trend toward a reduction in her serum glucagon levels as well. Based on the well-recognized association of PAX6 gene mutations with congenital aniridia, we screened the whole PAX6 coding sequence, leading to an identification of a heterozygous Gln135* mutation. We tested our idea that this mutation may at least in part explain the impaired insulin secretion observed in this patient. In cultured pancreatic β-cells, exogenous expression of the PAX6 Gln135* mutant produced a truncated protein that lacked the transcriptional activity to induce insulin gene expression. Our observation together with preceding reports support the recent attempt to include PAX6 in the growing list of genes causally responsible for monogenic diabetes. In addition, since most cases of congenital aniridia carry PAX6 mutations, we may need to pay more attention to blood glucose levels in these patients. Learning points: PAX6 Gln135* mutation may be causally associated not only with congenital aniridia but also with diabetes. Blood glucose levels may deserve more attention in cases of congenital aniridia with PAX6 mutations. Our case supports the recent attempt to include PAX6 in the list of MODY genes, and Gln135* may be pathogenic.